Adrenergic facilitation of GABAergic transmission in rat entorhinal cortex - Lei, Saobo; Deng, Pan-Yue; Porter, James E.; Shin, Hee-Sup (AMER PHYSIOLOGICAL SOC, 2007)
Whereas the entorhinal cortex (EC) receives noradrenergic innervations from the locus coeruleus of the pons and expresses adrenergic receptors, the function of norepinephrine (NE) in the EC is still elusive. We examined the effects of NE on GABA A receptor-mediated synaptic transmission in the superficial layers of the EC. Application of NE dose-dependently increased the frequency and amplitude of spontaneous inhibitory postsynaptic currents (IPSCs) recorded from the principal neurons in layer II/III through activation of alpha(1) adrenergic receptors. NE increased the frequency and not the amplitude of miniature IPSCs (mIPSCs) recorded in the presence of TTX, suggesting that NE increases presynaptic GABA release with no effects on postsynaptic GABA A receptors. Application of Ca2+ channel blockers (Cd2+ and Ni2+), omission of Ca2+ in the extracellular solution, or replacement of extracellular Na+ with N-methyl-D-glucamine (NMDG) failed to alter NE-induced increase in mIPSC frequency, suggesting that Ca2+ influx through voltage-gated Ca2+ or other cationic channels is not required. Application of BAPTA-AM, thapsigargin, and ryanodine did not change NE-induced increase in mIPSC frequency, suggesting that Ca2+ release from intracellular stores is not necessary for NE-induced increase in GABA release. Whereas alpha(1) receptors are coupled to G(q/11) resulting in activation of the phospholipase C (PLC) pathway, NE-mediated facilitation of GABAergic transmission was independent of PLC, protein kinase C, and tyrosine kinase activities. Our results suggest that NE-mediated facilitation of GABAergic function contributes to its antiepileptic effects in the EC.
Keywords: MEDIAL TEMPORAL-LOBE; PRESYNAPTIC INHIBITION; PHOSPHOLIPASE-C; SYNAPTIC-TRANSMISSION; PARAHIPPOCAMPAL REGION; INTRINSIC CONNECTIONS; RECEPTOR MODULATION; DENTATE GYRUS; HIPPOCAMPUS; NEURONS